1983
DOI: 10.1111/j.1471-4159.1983.tb13575.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Monensin on Posttranslational Processing of Myelin Proteins

Abstract: Rat brain slices were incubated with [3H]palmitic acid and [14C]glycine to label the lipid and protein moieties, respectively, of myelin proteolipid protein (PLP). The effects of monensin on posttranslational processing of proteins were examined by measuring the appearance of [14C]glycine- and [3H]palmitate-labeled proteins in myelin and myelin-like fractions. At 0.01 and 0.10 microM, monensin did not appreciably affect total lipid or protein synthesis; higher concentrations caused increased inhibition. Monens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Evidence exists suggesting that cerebroside sulfates and PLP are delivered to the myelin membrane through similar mechanisms. The transport of either of these components is disrupted by monensin (Townsend and Benjamins, 1983;Townsend et al, 1982Townsend et al, , 1984Sat0 et al, 1986) and by colchicine (Bizzozero et al, 1982b;Townsend et al, 1982Townsend et al, , 1984. Furthermore, recent studies from our laboratories strongly suggested the possibility of an associated or coupled transport of both components.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Evidence exists suggesting that cerebroside sulfates and PLP are delivered to the myelin membrane through similar mechanisms. The transport of either of these components is disrupted by monensin (Townsend and Benjamins, 1983;Townsend et al, 1982Townsend et al, , 1984Sat0 et al, 1986) and by colchicine (Bizzozero et al, 1982b;Townsend et al, 1982Townsend et al, , 1984. Furthermore, recent studies from our laboratories strongly suggested the possibility of an associated or coupled transport of both components.…”
Section: Discussionmentioning
confidence: 83%
“…Burkart et al (1982) suggested that cerebroside sulfates are transported in vesicles that are "pre myelin" membranes associated with lysosomes. There is ample experimental evidence demonstrating that using different substances such as colchicine (Bizzozero et al, 1982a) or monensin (Townsend and Benjamins, 1983), or in the absence of Caz++ or in the presence of C o 2 + + (Pasquini et al, 1987) it is possible to produce a marked decrease in the entry or assembly of either cerebroside sulfates or PLP into myelin. Recently, in our laboratory, we have been able to demonstrate that when the synthesis of cerebroside sulfates is inhibited with L cycloserine, the entry of PLP into myelin is also inhibited, suggesting that both constituents could be cotransported from their site of synthesis in the oligodendroglial cell to the myelin membrane (Pasquini et al, 1989).…”
Section: Introductionmentioning
confidence: 98%
“…Proteolipid protein (PLP) is the most abundant myelin protein, constituting about 50% of the total protein content in myelin (Lees and Brostoff, 1984). Studies carried out by several investigators have established that PLP is synthesized at the rough endoplasmic reticulum (RER), processed through the Golgi apparatus (Colman et al, 1982;Nussbaum and Roussel, 1983;Schwob et al, 1985) and transported in vesicles to the myelin membrane (Townsend and Benjamins, 1983). Although there are no lipids unique to myelin, these membranes are remarkably enriched in galactosyl cerebroside (GalCer) and sulfatide (Norton and Cammer, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Washed total lipid extracts of cerebral hemispheres, medulla oblongata and spinal cord of 10,20,30,40,90,, and 540 day old rats were prepared by the procedure of Folch et al (29). Content of PLP in washed lipid extracts was determined according to Lowry et al (30), modified by (31) and (32).…”
Section: Methodsmentioning
confidence: 99%
“…The content of proteolipid protein (PLP) in lipid extracts of brain during the development (8,9), its appearance and accumulation in the myelin (10)(11)(12) and other subcellular particles (13), as well as the changes of its amino acid composition (9,14) and the rate of turnover (15,16) were studied. In recent years an intensive study of problems concerning the synthesis of myelin PL, their posttranslational modification, transport and assembly into the myelin membrane has been expanded (17)(18)(19)(20). However, the properties and functions of PL in membranes are, probably, determined to a considerable extent by the lipid component of these complexes as well.…”
Section: Introductionmentioning
confidence: 99%